Basic education and hegemony in Turkey: thinking on ideology, policymaking and civil society - Karlidag-Dennis, Ecem (2018)
This thesis is concerned with the latest education reform, called 4+4+4 (4+), and overall educational changes in the basic education system (K12) since 2002 by the governing Justice and Development Party (AKP). The study investigates the role that education plays in state formation processes as well as looking at how dominant groups’ ideologies influence education policies. The research problem is the extent to which the state uses education policies to create a new public ideology. There are three key research questions that this thesis addresses. The data for this research was obtained from fifteen semi-structured interviews conducted with teacher trade unions, journalists and policy makers, focusing on their experiences and views not only about the 4+4+4 education system but also about the policymaking process in Turkey. The interviews present the pressing issues within the education system and indicate how education works a state apparatus for the government to gain and secure society’s consent. Located in a critical tradition, the research draws its theoretical framework from the Italian theorist Antonio Gramsci, especially focusing on his concepts of hegemony, civil society and consent. Using a Gramscian theoretical framework allows this study to place the 4+ reform in a bigger picture. The thesis analyses the reform not only from a local perspective but also from an international education policy perspective, focusing on the relationship between power, ideology and schooling. The findings suggest that the state and its private associations (i.e. media, and political parties) are actively encouraging Islamisation along with neoliberalism in order to consolidate their hegemonic dominance.